Absolute and Relative Quantification of Multiplex DNA Assays Based on an Elemental Labeling Strategy1. Issue 5 (12th December 2012) - Han, Guojun; Zhang, Sichun; Xing, Zhi; Zhang, Xinrong
<x xml:space="preserve">Abstract</x> Elements and quantification: A nucleic acid assay has been developed, based on an elemental labeling strategy using magnetic microparticles (MMPs), which provides quantification of multiple DNA targets. Rare‐earth elements, indium, and stable isotopes could be labeled with oligonucleotides serving as DNA probes. Quantitative analysis was then carried out using the designed systems (see picture) and elemental mass spectrometry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>